Acurácia da ultrassonografia à beira leito para prever desfecho da extubação de pacientes críticos: revisão sistemática de estudos diagnósticos - Araújo, Larissa Giovanna de Oliveira (2022)
The aim of this study was to systematically review the accuracy of diagnostic ultrasound to predict the outcomes of extubation in critically ill patients. Searches of studies between August 2021 and March 2022 were conducted in Pubmed, Embase, Cochrane, Web of Science, Lilacs, and Science Direct databases. Studies of diagnostic accuracy were included, with no language or publication date restrictions, with participants over 18 years of age, admitted to intensive care units, on mechanical ventilation for at least 24 hours, evaluated with the ultrasound prior to extubation. The search resulted in 47 references. Four indexes were found and evaluated. The cut-off points of the Lung Ultrasound Score ≤12, the diaphragmatic thickening fraction ≥30%, the diaphragmatic excursion ≥10 mm, and the Fast and Surface Respiration Index ≤1.6 resp/min/mm showed the highest diagnostic accuracy values. The results obtained with bedside ultrasound were useful in predicting the outcomes of ventilatory weaning.